Come eat : 100 nourishing recipes to eat every day - Ben-Ishay, Melissa (Harper Influence, an imprint of HarperCollins Publishers, 2026)
Mealtimes should be filled with nutritious dishes made to satisfy everyone at the table--including the pickiets of eaters--without sacrificing time. With helpful tips and easy-to-follow instructions, this book shows the reader how to adapt meals for everyone, from breaking down the components of a perfect salad to making soup with ingredients you already have in the fridge.